MANIFESTATIONS OF HIV AIDS IN CASE NEUROLOGY: EPIDEMIOLOGY STUDY AT SAIFUL ANWAR HOSPITAL YEAR 2013-2014 - Munir, Badrul; Candradikusuma, Didi (Malang Neurology Journal, 2015)
Background. Complications of HIV-AIDS cases neurological disorders are quite high and also very high mortality, but so far the data on disease epidemiology in Indonesia is still very limited.Objective. To determine the pattern of HIV-AIDS disease involving the nervous system in patients admitted to Saiful Anwar hospital.Methods. This prospective cohort study with a record of all patients with HIV-AIDS didagnosis manifest neurological disorders treated in an isolation room for HIV-AIDS Saiful Anwar Hospital for 1 year (September 2013- August 2014).Results. During 12 months acquired HIV-AIDS with neurological disorders as many as 23 patients (38.3% of all patients with an infection of the nervous system) with an average age of 48 years. Male gender 47.83%) and 52.17% of women. Number of CD4+ average of 24 / microliter, while the average number of leucocytes 9675/uL, while the most common sequence of disease; 39.1% of cerebral toxoplasmosis, tuberculosis meningoencephalitis 21.7%, 17.4% viral encephalitis, bacterial meningoencephalitis 13%, 4.3% dementia, cerebral abscess 4.3%. The mortality rate is still high, ranging from 57.6%.Conclusion. Manifestations of HIV AIDS in the field of neurology are very high, cerebral toxoplasmosis is the most common diagnosis, and correlated with the levels of CD4+. The mortality rate of HIV-AIDS cases manifesting high neurology.